(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
This article deals with the possibility of applying a non-prosecution agreement to criminal proceedings in progress when Law No. 13,964/2019 comes into force. The scope of the work is to analyze case law to verify the prevailing thesis on the subject, as well as the legal system as a whole, in order to identify the possibility of applying this institute, based in particular on the retroactivity of the most beneficial criminal law.